PERFORMANCE OF A 13MHZ CAVITY FOR AN RF IMPLANTER AT PEFP - Trịnh, Thị Tú Anh (2023)
A 13 MHz - normal conducting cavity for an rf implanter has been successfully developed at PEFP (Proton Engineering Frontier Project). It consists of an inductive coil, accelerating electrodes and a ground electrode for the inductor. Quality factor of 2074 and critical coupling were achieved at resonant frequency of 12.658MHz. Rf power of 1kW was forwarded to the cavity without any spark in the cavity. Beam test was then carried out with a 27keV helium beam generated from a Duoplasmatron ion source. The results showed that the helium beam was accelerated to final energy of 117 keV with energy spread of 1%. Detail experiments and results are addressed in this presentation.